2009
DOI: 10.1128/aem.01402-09
|View full text |Cite
|
Sign up to set email alerts
|

Improved Squalene Production via Modulation of the Methylerythritol 4-Phosphate Pathway and Heterologous Expression of Genes from Streptomyces peucetius ATCC 27952 in Escherichia coli

Abstract: Putative hopanoid genes from Streptomyces peucetius were introduced into Escherichia coli to improve the production of squalene, an industrially important compound. High expression of hopA and hopB (encoding squalene/phytoene synthases) together with hopD (encoding farnesyl diphosphate synthase) yielded 4.1 mg/liter of squalene. This level was elevated to 11.8 mg/liter when there was also increased expression of dxs and idi, E. coli genes encoding 1-deoxy-D-xylulose 5-phosphate synthase and isopentenyl diphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 20 publications
3
50
2
Order By: Relevance
“…Ten milliliters of the CM culturegrown mycelia were transferred to 50 ml of minimal medium (MM) (22) and grown for 96 h at 28°C and 250 rpm. Mycelia were used for extraction and quantification of ergosterol-squalene as previously reported (23,24). All measurements were made in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Ten milliliters of the CM culturegrown mycelia were transferred to 50 ml of minimal medium (MM) (22) and grown for 96 h at 28°C and 250 rpm. Mycelia were used for extraction and quantification of ergosterol-squalene as previously reported (23,24). All measurements were made in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Specific physicochemical and antioxidant properties of squalene imply also its applications in food industry, pharmacology, and cosmetics (for review, see Spanova & Daum, 2011). Another promising approach in the search for new squalene resources is the use of microorganisms as squalene producers on industrial scale (Ghimire et al, 2009;Nakazawa et al, 2012). Shark liver as the traditional source of squalene is currently being substituted by plant sources such as olive or amaranth oil (He & Corke, 2003;Garc ıa-González et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…4). These sequential reactions are catalysed by the FPP synthase, putatively encoded by hopD in S. peucetius [51, 52] and by SCO6763 in S. coelicolor [49, 53]. …”
Section: Synthesis Of Other Polar Lipidsmentioning
confidence: 99%
“…However, homologues to HpnC and HpnD are also present in Streptomyces peucetius – named there HopA and HopB, respectively – and each was reported to induce a small SQ accumulation when expressed in E. coli , suggesting that both are capable of independent synthesis of SQ, similar to the bifunctional eukaryotic SQ synthases [52]. This stands in contrast to the results by Pan et al [56] where it is reported that coexpression of HpnD, HpnC and HpnE from Zymomonas mobilis is required for SQ biosynthesis in E. coli .…”
Section: Synthesis Of Other Polar Lipidsmentioning
confidence: 99%